A Cross-State Analysis of Livelihood Security Among Farm Women in Kerala and Manipur - Ngasainao, Centy; Kaushal Kumar Jha (Indian Journal of Extension Education, 2025)
Farm women, having a pivotal role in agriculture, continue to face systemic barriers to livelihood security. This study was undertaken in 2022 to assess and compare the livelihood security, identify the constraints, and formulate a sustainable livelihood security framework for the farm women in Kerala and Manipur. Primary data were collected from 90 respondents using a pre-tested interview schedule and validated with key local informants through focus group discussions. Descriptive statistics, frequency, and Principal Component Analysis were used as statistical tools for data analysis. The findings revealed that 51.11% of the respondents in Kerala and 64.44 % in Manipur had a moderate level of livelihood security. The first two components, i.e., food and occupational security, could explain the total variance of 70.926 % for Kerala and 56.336 % for Manipur. The main constraints to livelihood security for farm women were insufficient funding and inadequate government support. Based on these findings, livelihood strategies were formulated for farm women and delivery system level to safeguard the livelihood outcomes. Designing interventions and policies aimed at ensuring farm women’s sustainable livelihood security will be significantly impacted by these findings and recommendations.